Impact of haemodialysis hours on outcomes in older patients. Issue 2 (30th November 2022) - Yeung, Emily K.; Brown, Leanne; Kairaitis, Lukas; Krishnasamy, Rathika; Light, Casey; See, Emily; Semple, David; Polkinghorne, Kevan R.; Toussaint, Nigel D.; MacGinley, Robert; Roberts, Matthew A.
Abstract: Aim: Previous studies report an association between longer haemodialysis treatment sessions and improved survival. Worldwide, there is a trend to increasing age among prevalent patients receiving haemodialysis. This analysis aimed to determine whether the mortality benefit of longer haemodialysis treatment sessions diminishes with increasing age. Methods: This was a retrospective cohort study of people who first commenced thrice‐weekly haemodialysis aged ≥65 years, reported to the Australia and New Zealand Dialysis and Transplant (ANZDATA) Registry from 2005 to 2015, included from 90 days after dialysis start. The primary outcome was all‐cause mortality. Cox regression analysis was performed with haemodialysis session duration the exposure of interest. Results: Of 8224 people who commenced haemodialysis as their first treatment for kidney failure aged ≥65 years during this period, 4727 patients died. Longer dialysis hours per session was associated with a decreased risk of death in unadjusted analyses [hazard ratio, HR, for ≥5 h versus 4 to <4.5 h: 0.81 (0.75–0.88, p < .001)]. Patients having longer dialysis sessions were younger but had greater co‐morbidity. In an adjusted model including age and other variables, the survival benefit of longer hours was only partially attenuated [HR for previous comparison: 0.75 (0.69–0.82, p < .001)], and no interaction between age and hours was demonstrated ( p = .89). Conclusion: The apparent survival benefit associated with longer haemodialysis session length appears to be preserved in patients 65 years or older. In practice, the benefit of longer dialysis hours should be carefully weighed against other factors in this patient group. Summary at a glance: The population of patients commencing haemodialysis at 65 years of age or older is increasing. While the observed benefit on mortality of longer haemodialysis session length was maintained in this group, 84% had at least one comorbidity, and withdrawal from haemodialysis for psychosocial reasons accounted for 19.9% of deaths.